Effects of shading and water availability on Kalanchoe pinnata (Lam.) Pers. (Crassulaceae) metabolite profile via a LC-MS-based untargeted metabolomics approach - Guilherme Perez Pinheiro; Álex Aparecido Rosini Silva; Andréia de Melo Porcari; Alexandra Christine Helena Frankland Sawaya (Journal of Plant Interactions)
Kalanchoe pinnata (Lam.) Pers. is a medicinal plant frequently used in folk medicine for treatment of inflammatory diseases and others. Several classes of bioactive compounds have been reported in extracts of this species, including flavonoids, which may increase/decrease in intensity according to environmental factors; therefore, we investigated the effects of shading and water availability treatments on the metabolic profile of extracts of K. pinnata analyzed via UHPLC-QTOF-MS. The overall metabolite profile was similar between conditions in both experiments, indicating that this species is not strongly affected by these cultivation conditions. However, conditions from both experiments affected specific metabolites listed herein, such as 4’,5,7-trihydroxy-3,6-dimethoxyflavone, a flavonoid that increased in shading conditions. From all metabolites, we annotated flavonoids, organic acids, and fatty acids, while the unidentified compounds were also reported for future investigation on this species’ metabolome. Finally, we provided new perspectives on the metabolism and cultivation conditions of K. pinnata.